Aspectos semânticos da terminologia do biodiesel - Pino, Douglas Henrique Perez (2010)
Nowadays we have been observing the expansion of knowledge mainly caused by continuous changes in science and its techniques. Terminology, as an academic subject concerned with the so-called specialized languages, play an important role in this process. The relevance of this research can be justified by the lack of systematic terminological repertoire for a strategic sector of the Brazilian economy, as biofuels/biodiesel. In this sense, our goals are: i) systematize the terminology of biodiesel in Portuguese in order to promote more efficient communication, allowing both scientific and technological information exchange among users and researchers of this area, as well as, generate resources for the subsequent creation of the first dictionary of this knowledge domain; ii) investigate biodiesel terminology from a semantic perspective, choosing the Qualia Structure, model of semantic structure which integrates Pustejovsky s Generative Lexicon Theory (1995) as a theoretical frame. In order to develop this research, the methodology used was based on the one elaborated and improved by GETerm, adopting descriptive terminology of linguistic base, specifically the postulates of the Communicative Theory of Terminology (CTT) (CABRÉ, 1999, 2003). As results of this investigation, we attained: a biodiesel corpus with approximately 1.5 million words, an ontology containing 280 terms and a repertoire of 50 definitions. At the end, we concluded that the application of Qualia Structure in terminological work may support the terminographic activity.